2016
DOI: 10.1038/srep25628
|View full text |Cite
|
Sign up to set email alerts
|

p53-dependent SIRT6 expression protects Aβ42-induced DNA damage

Abstract: Alzheimer’s disease (AD) is the most common type of dementia and age-related neurodegenerative disease. Elucidating the cellular changes that occur during ageing is an important step towards understanding the pathogenesis and progression of neurodegenerative disorders. SIRT6 is a member of the mammalian sirtuin family of anti-aging genes. However, the relationship between SIRT6 and AD has not yet been elucidated. Here, we report that SIRT6 protein expression levels are reduced in the brains of both the 5XFAD A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
76
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 60 publications
1
76
0
1
Order By: Relevance
“…Interestingly, research also shows that p53-dependent SIRT6 expression could protect against Aβ42-induced DNA damage [71]. Aβ 42 decreases SIRT6 and p53 levels, which is related to the JNK signaling pathway [71]. Overexpression of SIRT6 is shown to prevent Aβ42-induced DNA damage, and the SIRT6 activators could serve as a novel therapeutic target for AD and cancers.…”
Section: P53 Proteinmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, research also shows that p53-dependent SIRT6 expression could protect against Aβ42-induced DNA damage [71]. Aβ 42 decreases SIRT6 and p53 levels, which is related to the JNK signaling pathway [71]. Overexpression of SIRT6 is shown to prevent Aβ42-induced DNA damage, and the SIRT6 activators could serve as a novel therapeutic target for AD and cancers.…”
Section: P53 Proteinmentioning
confidence: 99%
“…It has been shown that SIRT6 expression is decreased in the brains of patients with Alzheimer's disease. Interestingly, research also shows that p53-dependent SIRT6 expression could protect against Aβ42-induced DNA damage [71]. Aβ 42 decreases SIRT6 and p53 levels, which is related to the JNK signaling pathway [71].…”
Section: P53 Proteinmentioning
confidence: 99%
See 3 more Smart Citations